The effects of high risk situations to the relapse process in alcohol dependence - Kalyoncu, Ö. Ayhan; Mırsal, Hasan; Pektaş, Özkan; Yazıcı, Ali Hilmi; Yalnız, Özlem; Beyazyürek, Mansur (Journal of Dependence, 2001)
Objective: To prevent to resume drinking alcohol is one of the main objectives of treatment in alcohol dependency. “High risk situations” is considered important in this study. It is suggested that detecting these high risk situations and learning to cope with them could assist to reduce relapse rates. In this study we intended todescribe risk concept, high risk situations and to investigate their effect on relaps course.Method: We included 40 alcoholic patients who relapsed after they completed their inpatient treatment program . All patients were males and they were all married or living with their female partners. In this study a semi-structured clinical assessment form was used to evaluate clinical and sociodemographic features. In order to determine high risk conditions we also used another questionaire. SPSS computer statistic program was used.Findings: There is a significant difference between groups in experiencing high risk conditions (X2 =66.3, df=4, p=0). In non-relapsing group risk concept was evaluated as important and avoidance behaviour from risk conditions was demonstrated. In relapsing group problems about receiving treatment consisted the main risk factor. Interestingly “experiencing social pressure" was found more often in non-relapsing group.Conclusions: It might help patients prevent relapses to detect high risk conditions. Our results suggest that problems about “receiving treatment” have important influence on the course of relapse. In spite of high social pressure seen in control group and low incidence of relapse might be related to the low incidence of problems encountered concerning “receiving appoppriate treatment”.
Keywords: Alcohol dependence; high risk situations; relapse